ANALYSIS OF TRAINING AND DEVELOPMENT FUNCTIONS IN IMPROVING PUBLIC SERVICE EFFECTIVENESS AT THE OFFICE OF THE NORTH GUNUNGSITOLI DISTRICT - Sonianto Duha; Fatolosa Hulu; Meiman Hidayat Waruwu; Odaligoziduhu Halawa (LPPM YPITI, 2026)
Employee training and development is a crucial function in human resource management that directly contributes to improving the quality of public services. At the Gunungsitoli Utara Sub-district Office, public services are at the forefront of government-community interactions, making employee competency crucial to service effectiveness. However, initial observations indicate that training and development activities at the office are limited and not systematically designed, potentially compromising service quality. This study aims to analyze the implementation of employee training and development and its impact on the effectiveness of public services at the Gunungsitoli Utara Sub-district Office. The method used is descriptive qualitative through interviews, observations, and documentation studies. The results show that training has been implemented through city and sub-district government programs, but still faces obstacles such as limited time, budget, materials that do not fully meet needs, and a lack of post-training evaluation. As a result, employee competency improvement is not optimal, so that public services are still hampered by speed, affordability, and public satisfaction. It is concluded that training needs to be designed more systematically, based on needs, supported by adequate resources, and equipped with continuous evaluation.